THE RELATION BETWEEN SOCIAL SUPPORT AND EMOTION-FOCUSED COPING IN DEAF ADOLESCENTS IN BOARDING SCHOOLS (Proceedings of International Conference on Special Education, 2019)
This study aims to determine the relation between social support and emotion-focused coping in Deaf adolescents in boarding schools. The research hypothesis shows that there is a negative and significant relation between social support and emotion-focused coping (distancing and escape-avoidance dimensions). The subjects in this study were 53 Deaf adolescents in boarding schools. The scales used were scale of social support (24 items, α = 0.934), scale of distancing dimension (6 items, α = 0.735), and scale of escape-avoidance dimension (6 items, α = 0.791) which were developed by the reseacher. The data were analyzed by using the correlation test of Spearman rho because the data distribution is not normal. The results show that social support is negatively correlated with emotion-focused coping dimensions. The distancing dimension (r = -0.447; p = 0.000) and escape-avoidance dimension (r = -0.451; p = 0.001).